Prediction of chemical composition and energy value of hay by near-infrared reflectance spectroscopy (NIRS) - Tomaž ŽNIDARŠIČ; Jože VERBIČ; Drago BABNIK (Acta Agriculturae Slovenica)
One hundred and fifty-eight hay samples with known chemical composition and in vitro determined concentration of net energy for lactation (NEL) were scanned over the wavelength range from 1100 to 2500 nm at 8 nm intervals. Calibration equations for the prediction of dry matter (DM), crude protein (CP), crude fibre (CF), crude fat, ash and NEL were developed by the use of principal component analysis. NIRS demonstrated high predictive ability for CP (R2 = 0.98), CF (R2 = 0.95) and ash (R2 = 0.94). Only moderate accuracy was characteristic for DM (0.87) and crude fat (R2 = 0.75). With exception of ash deviations from reference methods are comparable to those which are expected by the use of the same reference methods in different laboratories. NIRS has a high ability to predict in vitro assessed NEL concentration (R2 = 0.89). More than 95% of samples lied within acceptable limits of ± 0.3 MJ NEL kg–1 dry matter (DM). Despite suboptimal sample distribution, i.e. small number of samples in classes below 4.4 and above 5.6 MJ NEL kg–1 DM, the deviations of NIRS predicted values from reference values were not related to concentration of NEL. It was concluded that NIRS is rapid and reliable technique for determination of chemical composition and energy value of hay.